PENGARUH PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN PERENCANAAN PAJAK TERHADAP KINERJA KEUANGAN - Masyitah Masyitah; Achmad Uzaimi; Teddy Haryadi (Jurnal Ilmiah Akuntansi, 2026)
This study examines the determinants influencing the financial performance of food and beverage subsector companies in the post-pandemic economic recovery period. Using a quantitative approach, this research analyzes the impact of sales growth, firm size, and tax planning on Return on Assets (ROA) and Return on Equity (ROE). Data were obtained from the Indonesia Stock Exchange (IDX) for the 2021–2023 period, with 60 observations selected through purposive sampling criteria. Multiple linear regression analysis indicates that sales growth, firm size, and tax planning have a significant positive effect on financial performance, both partially and simultaneously. This demonstrates that effective operational management and tax strategy implementation directly enhance corporate profitability and market competitiveness.